2020
DOI: 10.3390/ma13204618
|View full text |Cite
|
Sign up to set email alerts
|

Tubular Dentin Regeneration Using a CPNE7-Derived Functional Peptide

Abstract: We aim to examine the effects of a newly developed peptide derived from CPNE7 (Cpne7-DP) in tertiary dentin formation and peritubular space occlusion, and comprehensively evaluate its potential as a bioactive therapeutic agent. Human dental pulp cells (HDPCs) and a mouse pre-odontoblast cell line, MDPC-23, were chosen for in vitro studies to characterize lineage-specific cell responses after Cpne7-DP treatment. Whether Cpne7-DP reproduces the dentin regenerative potential of CPNE7 was tested using a beagle dog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…All experiments using beagles were conducted under the guidelines provided by the Institutional Animal Care and Use Committee of Seoul National University (SNU-171020-5-2). The indirect pulp capping was performed as described previously ( Lee et al, 2020 ). Three beagle dogs (aged 1-2 y) were examined throughout the experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All experiments using beagles were conducted under the guidelines provided by the Institutional Animal Care and Use Committee of Seoul National University (SNU-171020-5-2). The indirect pulp capping was performed as described previously ( Lee et al, 2020 ). Three beagle dogs (aged 1-2 y) were examined throughout the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…This secreted factor from the pre-ameloblasts, binds to nucleolin on the cell surface of pre-odontoblasts and translocates to the nucleus, where it regulates dentin sialophosphoprotein ( Dspp ) expression ( Seo et al, 2017 ; Park et al, 2019 ). Of the numerous odontoblast differentiation-promoting factors reported so far, non-collagenous dentin matrix proteins ( Duque et al, 2006 ; Kim, 2017 ) and CPNE7 ( Choung et al, 2016 ; Lee et al, 2020 ) have been shown to form the physiological tubular dentin that contains the dentinal tubules that hold the odontoblast processes. However, the precise mechanism of CPNE7-mediated physiologic tubular dentin regeneration in adult dentin has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Another peptide is Cpne7-DP, which can be placed on 0.5% fibrin gel and then transplanted subcutaneously into immunocompromised mice. Twelve weeks after the transplantation, the Cpne7-DP treatment group showed the formation of dentin-pulp-like tissue with cells inserting long cellular processes into the tubule-like structure formed within newly mineralized tissue (Lee et al, 2020).…”
Section: Peptides For Dentin-pulp Complex Regenerationmentioning
confidence: 98%
“…In vitro analyses included the effects of the addition of the recombinant proteins or peptides on cell proliferation, differentiation, and Proliferation and differentiation of dental pulp cells Huang et al (2012) adhesion of postnatal human dental pulp cells (DPCs) In vivo analyses were completed following the insertion of agarose beads containing LRAP or LRAP 8, 9 into exposed cavity preparations of rat molars. After 8, 15, or 30 days' exposure, the pulp tissues were analyzed for changes in histomorphometry and cell proliferation by PCNA staining Copine 7 derived peptide (Cpne7-DP) (KYKQKRRSYK) Human dental pulp cells (HDPCs) and a mouse pre-odontoblast cell line, MDPC-23, were chosen for in vitro studies to characterize lineage-specific cell responses after Cpne7-DP treatment Promotes dentin regeneration, differentiation cellular Lee et al (2020) In vivo Cpne7-DP was tested using a beagle dog model by generating dentinal defects of various degrees. Overall mineralization capacity of Cpne7-DP was tested ex vivo PuraMatrix TM (RAD Ac-(RADA)4-NH2)…”
Section: Sld (Tdlqergdndispfsgdgqpfkd)mentioning
confidence: 99%
“…In a dentin hypersensitivity model, CPNE7 induced biological dentin sealing, and the effect was permanent rather than transient [22]. Subsequently, Lee et al synthesized CPNE7-derived oligopeptide (CPNE7-DP), which, as recombinant CPNE7 protein, also induced dentinal tubule occlusion [23].…”
Section: Introductionmentioning
confidence: 99%